Nanostructured Porous Silicon for Bone Tissue Engineering: Kinetics of Particle Degradation and Si-Controlled Release - Naveen Fatima; Hamideh Salehi; Eduardo J. Cueto-Díaz; Alban Desoutter; Frédéric Cuisinier; Frédérique Cunin; Pierre-Yves Collart-Dutilleul (Journal of Functional Biomaterials, 2023)
Nanostructured porous silicon (pSi) is a synthetic silicon-based material. Its biocompatibility and bioresorbability in body fluids make pSi an appealing biomaterial for tissue engineering, with surfaces characteristics facilitating human cell adhesion and differentiation. The resorption kinetics of such porous biomaterials is crucial for in vivo bone regeneration, in order to adapt biomaterial resorption to tissue formation, and to control the release of loaded bioactive molecules. We investigated pSi as a bioactive scaffold for bone tissue engineering, with an emphasis on kinetics of pSi resorption and silicon release. PSi particles and chips were fabricated from crystalline silicon, and functionalized by oxidation and chemical grafting of amine groups to mimic biological structures. Materials resorption over time was investigated with Raman spectroscopy, infrared spectroscopy, and Scanning Electron Microscopy. Silicon release was followed by mass spectrometry. Particle degradation and inclusion in newly formed bone were studied in vivo. The in vitro experiments revealed that non-oxidized pSi had an accelerated initial dissolution in ddH2O and an inhibition of initial Si release in SBF. This high reactivity also led to transformation towards amorphous non-resorbable silica when incubated in SBF. PSi resorption started immediately with a maximal dissolution in the first 24 h. Later, the dissolution rate decreased over time. In comparison, the resorption process of oxidized pSi seemed delayed, but more continuous. This delayed dissolution increased the bioactivity and stability, leading to enhanced bone formation in vivo. Delayed pSi degradation provided a constant surge of silicic acid over time and promoted bone regeneration, demonstrating the high potential of pSi for bone tissue engineering: Oxidized pSi were almost completely resorbed after 2 months of healing, with remaining partially dissolved particles surrounded by newly formed bone. On the contrary, non-oxidized particles were still obviously present after 2 months with limited bone regeneration. This delayed resorption is consistent with the in vitro observations in SBF, and particles’ transformation towards silica.